(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
This article highlights the theoretical and practical aspects of organizing a developmental educational environment in preschool educational institutions. The possibilities of forming cognitive activity, creativity, communicative competencies, and independent thinking in children through development centers are analyzed. In addition, the pedagogical effectiveness of the centers and their impact on the comprehensive development of the child are scientifically explained